EFFECT OF CIRCUIT TRAINING METHOD ON VERTICAL JUMP WOMEN IN VOLLEYBALL EXTRACURRICULAR ACTIVITIES AT MANIAMAS NGABANG HIGH SCHOOL - Wanda Firdaus; Eka Supriatna; Fitriana Puspa Hidasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThe problem in this study is the ability of vertical jumps in volleyball players at Maniamas Ngabang High School, who follow volleyball extracurricular activities are still categorized as less and the circuit training method has not been implemented yet. The purpose of this research is "is there any influence of the circuit training method on the ability of vertcal jump on volleyball extracurricular activities at Maniamas Ngabang High School. The purpose of this research is to improve the ability of vertical jumps. The population in this study were students who participated in extracurricular activities at Maniamas Ngabang High School, totaling 24 people. Sampling in this study uses a saturated sampling technique that is a sampling technique if all populations are used as samples. The form of research used in this study is the Pre Experimental Design with One-Group Pretest-Posttest Desingn model, the research design that is given a pretest before being given treatment, so the treatment results can be known more accurately. Based on the chi square test for pretest = 4.5154 and posttest = 0.6810 smaller than the chi squared table (5.991), then the statistical distribution of 24 athletes can be stated normal, the calculated F value is smaller than F table 1.24 < 2,022 for F table of 5% thus it can be concluded that the data variants to be analyzed are homogeneous. T test calculations obtained the value of t count = 20.51> t table = 1.17 and the results of the study were vertical jump exercises using the Circuit Training Method proved to have an effect on the jump height of students who took Volleyball Extracurricular at Maniamas Ngabang High School.Keywords: Circuit Training, Leg Muscle Power